Drug Abuse Prevention Campaigns in Chile (2004-2014): Between Prohibitionism and Stigmatisation (Communication & Society, 2019)
This paper studies the presence and reproduction of the ‘prohibitionist’ paradigm in the Chilean state’s drug policy by studying its drug abuse prevention campaigns. By means of a content analysis of the television spots broadcast between 2004 and 2014, the discursive and ideological elements present in these campaigns were examined. First and foremost, the results show that, despite institutional change and the creation of bodies such as the National Service for the Prevention and Rehabilitation of Drug and Alcohol Use (SENDA) and the National Council for Narcotics Control (CONACE), the state’s discourse has remained focused on the prohibitionist paradigm, resorting to highly stereotyped emotional messages. Secondly, drug consumption has been stigmatised and framed in profoundly dramatic contexts in which users belong to the criminal underworld or have physical and/or cognitive impairments. Thirdly, notwithstanding the fact that there are certain differences between the communication approaches employed by the SENDA and the CONACE, the discourses of both institutions are very uniform and reductionist. In order to design more efficient media campaigns, target audiences should be encouraged to analyse and ponder reflectively on the issue by conveying rational messages that contrast facts and data and offer a positive vision stressing the benefits of a healthy lifestyle.